Democracia como experimentalismo e experimentalismo como antidogmatismo: John Dewey e a teoria da educação hoje - Saharrea, Juan; Campeotto, Fabio; Viale, Claudio Marcelo (Cognitio: Revista de Filosofia, 2022)
The purpose of this paper is twofold: to reconstruct Dewey’s conception of experimentalism, mainly through his pedagogical writings, on the one hand; and to show the relevance of this reconstruction to current reassessments of Dewey’s political thought, on the other. The grounds for our perspective have a double character too. Firstly, we reconstruct the links between experimentalism and education on the basis of the first edition of How We Think (1910, MW 6), perhaps one of Dewey’s most noteworthy pedagogical texts. Secondly, we critically address three different reassessments of Dewey’s experimentalism in contemporary political thought, namely: 1) Pappas’s defense of Dewey’s substantive idea of democracy; 2) Forstenzer’s proposal of Deweyan experimentalism as an appropriate methodology for political philosophy; and 3) Anderson’s vindication of Deweyan experimental democracy in the context of social epistemology. It is sustained that in HWT Dewey places experimentalism as a kind of antidote against dogmatism and unreflective ways of reasoning. Thus, he links experimentalism with anti-dogmatism placing a special role in schooling for at least two reasons: 1) it is in the schooling phase that children are still sensitive to the development of certain habits; 2) dogmatism seems inevitable in any society but the educational phase is a key instance to try to avoid it. Neither (1) nor (2) are present in contemporary reassessments of Deweyan experimentalism.